Konstruksi Realitas Berita Lgbt Pada Media Online - Ramadhani, Esadella Unggulya; Pribadi, Farid (Paradigma, 2023)
From the findings of the data that has been obtained, cnnindonesia.com in reporting related to LGBT and LGBT couples at Citayam Fashion Week is very careful in reporting related to these two issues. In this news the choice of words and sentences tends not to lead to media symbolic violence. In media coverage, cnnindonesia.com also reports repeatedly but does not use obscure language or sentences. CNNIndonesia media in reporting related to LGBT by displaying responses from various parties such as the chairman of the MUI, legal experts, political figures and government officials. From the news carried out by the media, cnnindonesia.com highlighted related to state law regarding LGBT. This report focuses more on LGBT law because LGBT in Indonesia are considered deviant and same-sex marriage is considered illegal in Indonesia.